If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + 5) + -1ln(5) = ln(20) Reorder the terms: ln(5 + x) + -1ln(5) = ln(20) (5 * ln + x * ln) + -1ln(5) = ln(20) (5ln + lnx) + -1ln(5) = ln(20) Reorder the terms for easier multiplication: 5ln + lnx + -1 * 5ln = ln(20) Multiply -1 * 5 5ln + lnx + -5ln = ln(20) Reorder the terms: 5ln + -5ln + lnx = ln(20) Combine like terms: 5ln + -5ln = 0 0 + lnx = ln(20) lnx = ln(20) Reorder the terms for easier multiplication: lnx = 20ln Solving lnx = 20ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-20ln' to each side of the equation. -20ln + lnx = 20ln + -20ln Combine like terms: 20ln + -20ln = 0 -20ln + lnx = 0 Factor out the Greatest Common Factor (GCF), 'ln'. ln(-20 + x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-20 + x)' equal to zero and attempt to solve: Simplifying -20 + x = 0 Solving -20 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + x = 0 + 20 Combine like terms: -20 + 20 = 0 0 + x = 0 + 20 x = 0 + 20 Combine like terms: 0 + 20 = 20 x = 20 Add '-1x' to each side of the equation. x + -1x = 20 + -1x Combine like terms: x + -1x = 0 0 = 20 + -1x Simplifying 0 = 20 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5t-4=1+25t | | -6d^2+3cd+c-2d= | | (6y^2-7y+2)(4y-3)= | | 45x^2=20 | | y=2/3x^2-3 | | (11v+8)(3v-9)=0 | | 2x+5x=7x | | 9y+3z=34 | | 13x-27=9x-23 | | 13x-27=9x-23 | | 3x-11.2=x | | 0.6x-0.5y=2.4 | | -5x-34=-24 | | 8-9=5t^2 | | 24j-6=14j+7 | | -4x+20=-11 | | x-9y=28 | | 5x^2-10x/13x-26 | | (L-12)2=156 | | (3x+2)(3x^2-10x+7)=0 | | 3c^2-13c-16d^2= | | 12y-15=6y-10 | | L-12*2=156 | | (4-11i)(6+2i)= | | 5x^2-10x/13x=26 | | 2*12-L=156 | | 1/x^2-81 | | 6/2x-1 | | 4x^2+11s-3=0 | | 2*L-12=156 | | 44/180= | | -1/2x-7=-7 |